The Miaolingian, a new name for the 'Middle' Cambrian (Cambrian Series 3): identification of lower and upper boundaries in Baltoscandia. (3rd April 2019) - Nielsen, Arne Thorshøj; Ahlberg, Per
ABSTRACT: The Miaolingian is the new formal name for Cambrian Series 3 (≈ "Middle" Cambrian). The Global Stratotype Section and Point (GSSP) is defined in the Kaili Formation, Guizhou province, China, and is correlated by the First appearance Datum (FAD) of the trilobite Oryctocephalus indicus . However, this fossil has not been recorded from Baltoscandia. Here acritarchs may be used for identifying the base of the Miaolingian, but (1) Does the GSSP level in China correspond to the FAD of the Eliasum – Cristallinium acritarch assemblage? and (2) How accurately is the incoming of this assemblage identified in Baltoscandian sections? Comparison of acritarchs shared between the GSSP section and Baltica indicates that the GSSP correlates with a level within the Baltoscandian Eliasum – Cristallinium assemblage zone. Nonetheless, it appears most feasible to consider the base of this zone (i.e., the base of the Kibartian Regional Stage) as the best possible local approximation for the base of the Miaolingian. This level equates the traditional lower boundary of the "Middle" Cambrian used in East Europe. In much of Scandinavia, the lower boundary of the Miaolingian thus identified falls within the Hawke Bay hiatus. Hence, the Miaolingian by and large corresponds to the interval that previously has been assigned to the "Middle" Cambrian in the region, except that the Miaolingian includes the Agnostus pisiformis Zone, traditionally assigned to the "Upper" Cambrian. In Scandinavia, the Miaolingian/Furongian boundary is precisely defined, being marked by the incoming of Glyptagnostus reticulatus and abundant olenid trilobites. In the East Baltic area, the upper boundary of the Miaolingian coincides with a major unconformity.